Gestión de Calidad de los Servicios Para Mejorar el Desempeño Laboral en el Hotel Riobamba Inn. de la Ciudad de Riobamba - Rodríguez Naranjo, Byron Patricio (2019)
The purpose of this research work is to determine the Quality Management System of the Services Based on the ISO 9001-2008, with the objective of improving the Work Performance in the Riobamba Inn. Hotel in the City of Riobamba, and increase the business profitability, reducing expenses, and improve its competitive level with respect to other hotels in the city. The research work begins by addressing the existing problem in the hotel, describing the research methodology, through a SWOT analysis which allow us to make the current situational diagnosis, obtaining the results that let us propose action plans against the identified problems. Finally, the proposal is shown based on what the APA Standard requires, the development of a quality manual model, with procedures and the setting up of the members that guarantee the functioning of the service quality management system. The implementation of a service quality management system, shall let us to improve work performance, setting out a clear and concise work structure of each member and achieve ongoing improvements in order to accomplish their goals.